Low-cost preparation method of high-performance titanium-doped iron phosphate
By doping titanium elements in the wet reaction stage and controlling the pH value of the phosphorus salt solution, the preparation process of iron phosphate is simplified, and the problem of improving the conductivity and compaction density of lithium iron phosphate in the prior art is solved, and high performance is achieved Material preparation and process simplification.
Patent Information
- Application Number
- CN202411798340.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art has limitations in improving the conductivity and compaction density of lithium iron phosphate, and the process is complex, the cycle is long and the reaction conditions are harsh, which increases the wastewater treatment pressure.
Using a low-cost preparation method of high-performance titanium doped iron phosphate, the doping of titanium elements and iron phosphate is achieved by adding ferrous salt and titanium salt solution in the wet reaction stage and controlling the pH value of the phosphorus salt solution. Synthesis avoids the use of template agents and complex agents, and simplifies the process flow.
The high powder compaction density and excellent electrochemical properties of lithium iron phosphate materials have been achieved. The discharge capacity of 0.1C reaches 156.35 mAh/g, and the discharge capacity of 1C reaches 131.47 mAh/g. The process is simple and the cost is low, making it suitable for industrial production.
Smart Images

Figure CN119390030A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a low-cost preparation method for high-performance titanium-doped iron phosphate. Background Art
[0002] At present, there are three main methods to improve the conductivity of lithium iron phosphate: particle nano-sizing, conductive material coating and metal ion doping. Among them, particle nano-sizing will limit the improvement of product compaction density; conductive material coating has limited improvement on the conductivity inside the particles; only metal ion doping can establish internal conductive channels without affecting the compaction density of the product and simultaneously improve the capacity. In addition, advancing the metal ion doping step to the synthesis stage of the precursor iron phosphate is conducive to improving the uniformity of bulk doping and achieving an increase in the conductivity of lithium iron phosphate.
[0003] On the other hand, the compaction density of lithium iron phosphate needs to be improved to solve the problem of its low energy density. The existing technology mainly takes measures such as controlling the microscopic morphology, particle size distribution and element doping of its precursor iron phosphate. Among them, the technical solution provided by the present invention mainly involves element doping, and the specific related technical solutions are briefly described as follows: The patent "A method for preparing high-purity and high-pressure compacted iron phosphate for lithium iron phosphate, CN 109775679A" adopts a two-step method, wherein slurry A and slurry B are stirred and mixed in a pressure vessel in a certain proportion to obtain slurry C, and then slurry C is obtained through aging, filtration, washing and other steps, and then atomized and granulated to obtain high-purity and high-pressure compacted anhydrous iron phosphate. The compacted density of lithium iron phosphate prepared from this raw material exceeds 2.4 g / cm 3 .
[0004] Patent "Preparation Method of Composite Structure Orthoferric Phosphate for High Capacity and High Compacted Lithium Iron Phosphate, CN 110436427B" introduces complexing agent and template agent, uses coprecipitation method to synthesize iron phosphate hydrate precursor, and controls the feed rate, stirring frequency, stirring time and reaction temperature to achieve effective control of iron phosphate morphology and particle size distribution, and obtains iron phosphate with different morphologies and wide particle size distribution range of flaky and granular composite structures. The lithium iron phosphate prepared from this precursor material has a greatly improved compaction density.
[0005] The patent "A high-pressure dense iron phosphate and its preparation method, CN 114314541A" adopts a two-step method. First, the prepared small-particle dihydrate iron phosphate is ground to 0.5-2.0 um to obtain iron phosphate seeds, and then a synthesis reaction is carried out to obtain grown dihydrate iron phosphate particles based on the iron phosphate seeds. After sintering, screening and other steps, anhydrous iron phosphate with a wide particle size distribution is obtained, which is used for the synthesis of lithium iron phosphate, effectively improving the compaction density of lithium iron phosphate.
[0006] However, most of the above technologies regulate the microstructure and particle size distribution of iron phosphate materials in a step-by-step manner. Some technologies even require the introduction of templates, chelating agents and other additives that will increase the pressure of wastewater treatment, or have disadvantages such as long process cycles and harsh reaction conditions. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a low-cost preparation method of high-performance titanium-doped iron phosphate to improve the conductivity and compaction density of lithium iron phosphate materials. The technical solution provided by the present invention does not require the introduction of additives such as templates and complexing agents that will increase the pressure of wastewater treatment, nor does it require a step-by-step method to prepare high-performance iron phosphate materials as in the relevant patents, thereby shortening the process flow and production cycle and facilitating quality management, as follows: A low-cost preparation method for high-performance titanium-doped iron phosphate comprises the following steps: S1, respectively prepare 40-85 wt% phosphoric acid solution, 10-25 wt% hydrogen peroxide solution, phosphate solution and ferrous salt solution for standby use; the concentration of phosphorus in the phosphate solution is 0.8-1.3 mol / L; the concentration of iron in the ferrous salt solution is 0.8-1.3 mol / L; S2. Add titanium sulfate directly to the ferrous salt solution, stir evenly, and control the solution pH to 2.0-3.0 to obtain an iron-titanium mixed solution; S3, directly add ammonia water to the phosphate solution, stir evenly, control the solution pH to 5.95-6.05, add hydrogen peroxide solution to obtain a phosphorus-oxygen mixed solution; S4. Under continuous stirring, the temperature of the iron-titanium mixed solution is raised to 40-60° C., and a phosphorus-oxygen mixed solution is added to gradually oxidize all ferrous ions into trivalent ferrous ions. After reacting for 30 minutes, slurry A is obtained. S5, slurry A is initially filtered and washed to obtain filter cake A; S6. Under continuous stirring, add pure water and phosphoric acid solution to the filter cake A, then raise the temperature to 80-100° C., and keep the temperature for 60-120 min after the slurry color changes to white, to obtain white slurry B; S7. After filtering, washing and drying the slurry B, titanium-doped iron phosphate dihydrate is obtained. After calcining the iron phosphate dihydrate, high-purity and high-density anhydrous iron phosphate is obtained.
[0008] Moreover, in step S1, the phosphate salt solution is prepared from one or any combination of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.
[0009] Moreover, in step S1, the phosphate solution is prepared from phosphoric acid, and ammonia water or liquid alkali is added to adjust the pH value to 4.0-6.0.
[0010] Moreover, in step S1, the ferrous salt solution is prepared from one or any combination of ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder, and iron sheet.
[0011] Moreover, in step S2, the pH value of the iron-titanium mixed solution is controlled by a sulfuric acid solution.
[0012] Moreover, in step S3, the pH value of the phosphate solution is controlled by ammonia water; the molar ratio of the added hydrogen peroxide to the phosphorus element in the phosphate solution is 0.6:1-0.7:1.
[0013] Moreover, in step S4, the phosphorus-oxygen mixed solution is added within 50-60 minutes.
[0014] Moreover, in step S4, the molar ratio of iron element to phosphorus element in the iron-titanium mixed solution and the phosphorus-oxygen mixed solution is 1:0.9-1:1.1.
[0015] Moreover, in step S5, the conductivity of the washing water of the slurry A after preliminary filtration and washing is ≤2000 μS / cm.
[0016] Moreover, in step S6, the molar ratio of phosphorus in the phosphoric acid solution to iron in the slurry A solution should be controlled to be n(P):n(Fe)=0.2:1-0.4:1; and the heating time is 90-110 min.
[0017] The present invention can prepare a titanium-doped iron phosphate material with a composite structure of large and small particles by a simple method, and the corresponding lithium iron phosphate has a higher powder compaction density and electrical properties. The principle is: ① In the wet reaction stage, ferrous salt and titanium salt solution were used as the base solution, and a mixed solution of phosphate and hydrogen peroxide was used as the feed solution, so that trace titanium was successfully doped into the iron phosphate lattice to replace part of the Fe position. According to the metal bond theory, the binding energy between titanium ions and oxygen is greater than that between iron ions and oxygen. Therefore, the unit cell where the titanium ions are located is more tightly bound, and the primary particle size composed of the unit cell is smaller, so titanium doping will cause the primary particles of iron phosphate to shrink; ② The reaction of synthesizing iron phosphate is an exothermic reaction. The reaction speed is accelerated at high temperature, which is conducive to the formation of small particles; ③ Use a pH neutralizer to make the pH of the phosphate salt greater than 6.0, so that the pH of the reaction process is greater than 1.5, and the supersaturation of the reaction solution is moderate, which is conducive to the formation of larger particles; ④ After the obtained iron phosphate is made into lithium iron phosphate, the titanium ions in the iron phosphate will reduce the diffusion barrier of lithium ions through the b-axis in the lithium iron phosphate lattice, thereby increasing the lithium ion diffusion conductivity and improving the conductivity of the lithium iron phosphate material.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes a preparation process for synthesizing titanium-doped iron phosphate using a trivalent iron solution Fenton system. The synthesized iron phosphate has a compact and dense morphology, and the pores inside the primary particles are still abundant. The lithium iron phosphate material obtained after grinding and sintering can ensure that the powder compaction density reaches a high level of 2.613 g / cc, and a certain amount of small particles provide better electrical properties. The 0.1C discharge capacity can still reach 156.35 mAh / g, and the 1C discharge capacity reaches 131.47 mAh / g.
[0019] Compared with other technologies for regulating the microscopic morphology of iron phosphate, the present invention only requires adding a trace amount of titanium salt and adjusting the pH of the phosphate salt to prepare a titanium-doped iron phosphate material with a composite structure of large and small particles through a conventional controlled crystallization method, thereby avoiding the disadvantage of maintaining the reaction pH by real-time adjustment of the neutralizer feed rate, which leads to difficult operation; avoiding the harsh reaction conditions of the hydrothermal method such as high temperature and high pressure; avoiding the addition of surfactants in the reaction system, reducing the pressure of wastewater treatment; and avoiding the disadvantage of consuming a large amount of neutralizer.
[0020] The present invention does not require precise control of the reaction pH, does not require the addition of additional surfactants, and does not require the customization of special reaction equipment. It only requires the addition of a trace amount (ppm level) of titanium salt and the use of a controlled crystallization method to prepare a titanium-doped high-density iron phosphate material with a composite structure of large and small particles, which is suitable for industrial production.
[0021] Compared with the conventional ferric phosphate preparation technology, the present invention uses Ti doped in the wet synthesis process. 4+ , using Ti 4+ Changing and optimizing the primary particle size of iron phosphate; at the same time, changing the crystal structure of iron phosphate, which is beneficial to Li after being made into lithium iron phosphate + transmission, thus improving the electrochemical performance of the positive electrode material.
[0022] The present invention has excellent repeatability, and various data of ferric phosphate dihydrate and anhydrous ferric phosphate obtained through a large number of experiments are very stable, which proves that the present invention has a large process window and is suitable for industrial production.
[0023] 6. The raw materials required for the present invention, such as phosphoric acid, are not used in large quantities and are cheap and readily available, and are suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron micrograph of the iron phosphate dihydrate prepared in Experiment 1; Figure 2 This is a scanning electron micrograph of the iron phosphate dihydrate prepared in Experiment 1; Figure 3 Particle size distribution diagram of anhydrous iron phosphate prepared for Experiment 1; Figure 4 Scanning electron micrograph of iron phosphate dihydrate prepared for Experiment 2; Figure 5 Scanning electron micrograph of iron phosphate dihydrate prepared for Experiment 2; Figure 6 Particle size distribution diagram of anhydrous iron phosphate prepared for Experiment 2; Figure 7 Scanning electron micrograph of iron phosphate dihydrate prepared for Experiment 3; Figure 8 Scanning electron micrograph of iron phosphate dihydrate prepared for Experiment 3; Fig. 9 Particle size distribution diagram of anhydrous iron phosphate prepared for Experiment 3; Fig.10 SEM image of iron phosphate dihydrate prepared for Experiment 4; Fig.11 SEM image of iron phosphate dihydrate prepared for Experiment 4; Fig.12 Particle size distribution diagram of anhydrous iron phosphate prepared for Experiment 4; Fig.13 SEM image of iron phosphate dihydrate prepared for Experiment 5; Fig.14 SEM image of iron phosphate dihydrate prepared for Experiment 5; Fig.15 Particle size distribution of anhydrous iron phosphate prepared for Experiment 5. DETAILED DESCRIPTION
[0025] Example 1 A low-cost preparation method for high-performance titanium-doped iron phosphate comprises the following steps: S1, prepare 40wt% phosphoric acid solution, 10wt% hydrogen peroxide solution, phosphate solution and ferrous salt solution respectively, and set aside; the concentration of phosphorus in the phosphate solution is 0.8mol / L; the concentration of iron in the ferrous salt solution is 0.8mol / L; S2. Add titanium sulfate directly to the ferrous salt solution, stir evenly, and control the solution pH to 2.0 to obtain an iron-titanium mixed solution; S3, directly add ammonia water to the phosphate solution, stir evenly, control the solution pH=5.95, add hydrogen peroxide solution to obtain a phosphorus-oxygen mixed solution; S4. Under continuous stirring, the temperature of the iron-titanium mixed solution was raised to 40° C., and a phosphorus-oxygen mixed solution was added to gradually oxidize all the ferrous ions into trivalent ferrous ions. After reacting for 30 minutes, slurry A was obtained. S5, slurry A is initially filtered and washed to obtain filter cake A; S6. Under continuous stirring, pure water and phosphoric acid solution were added to the filter cake A, and then the temperature was raised to 80° C. After the slurry color turned white, the temperature was kept for 60 minutes to obtain a white slurry B; S7. After filtering, washing and drying the slurry B, titanium-doped iron phosphate dihydrate is obtained. After calcining the iron phosphate dihydrate, high-purity and high-density anhydrous iron phosphate is obtained.
[0026] Furthermore, in step S1, the phosphate solution is prepared from ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.
[0027] Furthermore, in step S1, the phosphate salt solution is prepared from phosphoric acid, and ammonia water or liquid alkali is added to adjust the pH value to 4.0.
[0028] Furthermore, in step S1, the ferrous salt solution is prepared from ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder and iron sheet.
[0029] Furthermore, in step S2, the pH value of the iron-titanium mixed solution is controlled by a sulfuric acid solution.
[0030] Furthermore, in step S3, the pH value of the phosphate solution is controlled by ammonia water; the molar ratio of the added hydrogen peroxide to the phosphorus element in the phosphate solution is 0.6:1.
[0031] Furthermore, in step S4, the phosphorus-oxygen mixed solution is added within 50 minutes.
[0032] Furthermore, in step S4, the molar ratio of iron element to phosphorus element in the iron-titanium mixed solution and the phosphorus-oxygen mixed solution is 1:0.9.
[0033] Furthermore, in step S5, the conductivity of the washing water of the slurry A after preliminary filtration and washing is ≤2000 μS / cm.
[0034] Furthermore, in step S6, the molar ratio of phosphorus in the phosphoric acid solution to iron in the slurry A solution should be controlled to be n(P):n(Fe)=0.2:1; and the heating time is 90 min.
[0035] Example 2 A low-cost preparation method for high-performance titanium-doped iron phosphate comprises the following steps: S1, prepare 85 wt% phosphoric acid solution, 25 wt% hydrogen peroxide solution, phosphate solution and ferrous salt solution respectively, and set them aside; the concentration of phosphorus in the phosphate solution is 1.3 mol / L; the concentration of iron in the ferrous salt solution is 1.3 mol / L; S2. Add titanium sulfate directly to the ferrous salt solution, stir evenly, and control the solution pH to 3.0 to obtain an iron-titanium mixed solution; S3, directly add ammonia water to the phosphate solution, stir evenly, control the solution pH=6.05, add hydrogen peroxide solution to obtain a phosphorus-oxygen mixed solution; S4. Under continuous stirring, the temperature of the iron-titanium mixed solution was raised to 60° C., and a phosphorus-oxygen mixed solution was added to gradually oxidize all ferrous ions into trivalent ferrous ions. After reacting for 30 minutes, slurry A was obtained. S5, slurry A is initially filtered and washed to obtain filter cake A; S6. Under continuous stirring, pure water and phosphoric acid solution were added to the filter cake A, and then the temperature was raised to 100° C. After the slurry color changed to white, the temperature was kept for 120 min to obtain a white slurry B; S7. After filtering, washing and drying the slurry B, titanium-doped iron phosphate dihydrate is obtained. After calcining the iron phosphate dihydrate, high-purity and high-density anhydrous iron phosphate is obtained.
[0036] Furthermore, in step S1, the phosphate salt solution is prepared from ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and sodium monohydrogen phosphate.
[0037] Furthermore, in step S1, the phosphate salt solution is prepared from phosphoric acid, and ammonia water or liquid alkali is added to adjust the pH value to 6.0.
[0038] Furthermore, in step S1, the ferrous salt solution is prepared from ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder and iron.
[0039] Furthermore, in step S2, the pH value of the iron-titanium mixed solution is controlled by a sulfuric acid solution.
[0040] Furthermore, in step S3, the pH value of the phosphate solution is controlled by ammonia water; the molar ratio of the added hydrogen peroxide to the phosphorus element in the phosphate solution is 0.7:1.
[0041] Furthermore, in step S4, the phosphorus-oxygen mixed solution is added within 60 minutes.
[0042] Furthermore, in step S4, the molar ratio of iron element to phosphorus element in the iron-titanium mixed solution and the phosphorus-oxygen mixed solution is 1:1.1.
[0043] Furthermore, in step S5, the conductivity of the washing water of the slurry A after preliminary filtration and washing is ≤2000 μS / cm.
[0044] Furthermore, in step S6, the molar ratio of phosphorus in the phosphoric acid solution to iron in the slurry A solution should be controlled to be n(P):n(Fe)=0.4:1; and the heating time is 110 min.
[0045] Example 3 A low-cost preparation method for high-performance titanium-doped iron phosphate comprises the following steps: S1, prepare 60 wt% phosphoric acid solution, 18 wt% hydrogen peroxide solution, phosphate solution and ferrous salt solution respectively, and set them aside; the concentration of phosphorus in the phosphate solution is 1.0 mol / L; the concentration of iron in the ferrous salt solution is 1.0 mol / L; S2. Add titanium sulfate directly to the ferrous salt solution, stir evenly, and control the solution pH to 2.5 to obtain an iron-titanium mixed solution; S3, directly add ammonia water to the phosphate solution, stir evenly, control the solution pH=6.0, add hydrogen peroxide solution to obtain a phosphorus-oxygen mixed solution; S4. Under continuous stirring, the temperature of the iron-titanium mixed solution was raised to 50° C., and a phosphorus-oxygen mixed solution was added to gradually oxidize all ferrous ions into trivalent ferrous ions. After reacting for 30 minutes, slurry A was obtained. S5, slurry A is initially filtered and washed to obtain filter cake A; S6. Under continuous stirring, pure water and phosphoric acid solution were added to the filter cake A, and then the temperature was raised to 90° C. After the slurry color turned white, the temperature was kept for 90 min to obtain a white slurry B; S7. After filtering, washing and drying the slurry B, titanium-doped iron phosphate dihydrate is obtained. After calcining the iron phosphate dihydrate, high-purity and high-density anhydrous iron phosphate is obtained.
[0046] Furthermore, in step S1, the phosphate salt solution is prepared from ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and sodium monohydrogen phosphate.
[0047] Furthermore, in step S1, the phosphate salt solution is prepared from phosphoric acid, and ammonia water or liquid alkali is added to adjust the pH value to 5.0.
[0048] Furthermore, in step S1, the ferrous salt solution is prepared from ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder and iron sheet.
[0049] Furthermore, in step S2, the pH value of the iron-titanium mixed solution is controlled by a sulfuric acid solution.
[0050] Furthermore, in step S3, the pH value of the phosphate salt solution is controlled by ammonia water; the molar ratio of the added hydrogen peroxide to the phosphorus element in the phosphate salt solution is 0.65:1.
[0051] Furthermore, in step S4, the phosphorus-oxygen mixed solution is added within 55 minutes.
[0052] Furthermore, in step S4, the molar ratio of iron element to phosphorus element in the iron-titanium mixed solution and the phosphorus-oxygen mixed solution is 1:1.0.
[0053] Furthermore, in step S5, the conductivity of the washing water of the slurry A after preliminary filtration and washing is ≤2000 μS / cm.
[0054] Furthermore, in step S6, the molar ratio of phosphorus in the phosphoric acid solution to iron in the slurry A solution should be controlled to be n(P):n(Fe)=0.3:1; and the heating time is 100 min.
[0055] Experimental Section
[0056] Experiment 1 This experiment adopts the technical solution of the present invention, a low-cost preparation method of high-performance titanium-doped iron phosphate, comprising the following steps: (1) Weigh 2.76 kg of ammonium dihydrogen phosphate, dissolve it and dilute it to 15 L to obtain a phosphate solution; weigh 6.67 kg of ferrous sulfate heptahydrate, dissolve it and dilute it to 20 L to obtain a ferrous salt solution; (2) Weigh 29.0 g of titanium sulfate and directly add it to the above ferrous salt solution and quickly stir it evenly. Control the pH of the iron-titanium mixed solution to 2.4 by adding concentrated sulfuric acid solution; (3) under continuous stirring, adding concentrated ammonia water in small amounts to the above phosphate solution several times to control the pH of the phosphate solution to 6.0, directly adding 1607.5 g of 30 wt% hydrogen peroxide solution thereto, and finally adding pure water to make the volume to 18.5 L to obtain a phosphorus-oxygen mixed solution; (4) The iron-titanium mixed solution was heated to 50°C, and under continuous stirring, the phosphorus-oxygen mixed solution was slowly added within 60 minutes to qualitatively detect whether all ferrous ions were oxidized to trivalent ferrous ions; the mixture was then reacted for 30 minutes to obtain slurry A; (5) After the reaction is completed, the slurry A is preliminarily washed in a centrifuge and dried at high speed to obtain a filter cake A; (6) Add a certain amount of pure water to the filter cake A, continue stirring until the slurry is uniform, continue to add 738.52 g of 80 wt% phosphoric acid solution, then raise the temperature to 93 °C and keep it for 2 h to obtain white slurry B; (7) After filtering, washing and drying, slurry B is used to obtain titanium-doped iron phosphate dihydrate. After calcining, the iron phosphate dihydrate is used to obtain anhydrous iron phosphate with high purity and high compaction density.
[0057] Figure 1Scanning electron microscope image of iron phosphate dihydrate prepared in Experiment 1. Figure 2 Scanning electron microscope image of iron phosphate dihydrate prepared in Experiment 1. Figure 3 Particle size distribution diagram of anhydrous iron phosphate prepared for Experiment 1; Figure 1-3 It can be seen that the primary particles of ferric phosphate dihydrate prepared in Experiment 1 aggregate into flake agglomerates, and the flakes are stacked on each other to form a cluster structure; the primary particles of anhydrous ferric phosphate are melt-bonded to form a porous network structure; the particle size distribution is bimodal, with a composite of large and small particles.
[0058] Experiment 2 This experiment adopts the technical solution of the present invention, a low-cost preparation method of high-performance titanium-doped iron phosphate, comprising the following steps: (1) Weigh 2.76 kg of ammonium dihydrogen phosphate, dissolve it and dilute it to 15 L to obtain a phosphate solution; weigh 6.67 kg of ferrous sulfate heptahydrate, dissolve it and dilute it to 20 L to obtain a ferrous salt solution; (2) Weigh 31.1 g of titanium sulfate and directly add it to the above ferrous salt solution and quickly stir it evenly. Control the pH of the iron-titanium mixed solution to 2.35 by adding concentrated sulfuric acid solution; (3) under continuous stirring, adding concentrated ammonia water in small amounts to the above phosphate solution several times to control the pH of the phosphate solution to 5.86, directly adding 1607.5 g of 30 wt% hydrogen peroxide solution thereto, and finally adding pure water to make the volume to 18.5 L to obtain a phosphorus-oxygen mixed solution; (4) The iron-titanium mixed solution was heated to 50°C, and under continuous stirring, the phosphorus-oxygen mixed solution was slowly added within 60 minutes to qualitatively detect whether all ferrous ions were oxidized to trivalent ferrous ions; the mixture was then reacted for 30 minutes to obtain slurry A; (5) After the reaction is completed, the slurry A is preliminarily washed in a centrifuge and dried at high speed to obtain a filter cake A; (6) Add a certain amount of pure water to the filter cake A, continue stirring until the slurry is uniform, continue to add 739.06 g of 80 wt% phosphoric acid solution, then raise the temperature to 93 °C and keep it for 2 h to obtain white slurry B; (7) After filtering, washing and drying, slurry B is used to obtain titanium-doped iron phosphate dihydrate. After calcining, the iron phosphate dihydrate is used to obtain anhydrous iron phosphate with high purity and high compaction density.
[0059] Figure 4 Scanning electron microscope image of iron phosphate dihydrate prepared for experiment 2, Figure 5 Scanning electron microscope image of iron phosphate dihydrate prepared for experiment 2, Figure 6 Particle size distribution diagram of anhydrous iron phosphate prepared for Experiment 2; Figure 4-6It can be seen that the primary particles of ferric phosphate dihydrate prepared in Experiment 2 aggregate into flaky agglomerates, and the flaky particles are stacked on each other to form a cluster structure; the primary particles of anhydrous ferric phosphate are melt-bonded to form a porous network structure; the particle size distribution is bimodal, with a composite of large and small particles, similar to Experiment 1.
[0060] Experiment 3 This experiment adopts the technical solution of the present invention, a low-cost preparation method of high-performance titanium-doped iron phosphate, comprising the following steps: (1) Weigh 2.76 kg of ammonium dihydrogen phosphate, dissolve it and dilute it to 15 L to obtain a phosphate solution; weigh 6.67 kg of ferrous sulfate heptahydrate, dissolve it and dilute it to 20 L to obtain a ferrous salt solution; (2) Weigh 31.1 g of titanium sulfate and directly add it to the above ferrous salt solution and quickly stir it evenly. Control the pH of the iron-titanium mixed solution to 2.35 by adding concentrated sulfuric acid solution; (3) under continuous stirring, adding concentrated ammonia water in small amounts to the above phosphate solution several times to control the pH of the phosphate solution to 6.0, directly adding 1607.5 g of 30 wt% hydrogen peroxide solution thereto, and finally adding pure water to make the volume to 18.5 L to obtain a phosphorus-oxygen mixed solution; (4) The iron-titanium mixed solution was heated to 50°C, and under continuous stirring, the phosphorus-oxygen mixed solution was slowly added within 60 minutes to qualitatively detect whether all ferrous ions were oxidized to trivalent ferrous ions; the mixture was then reacted for 30 minutes to obtain slurry A; (5) After the reaction is completed, the slurry A is preliminarily washed in a centrifuge and dried at high speed to obtain a filter cake A; (6) Add a certain amount of pure water to the filter cake A, continue stirring until the slurry is uniform, continue to add 749.51 g of 80 wt% phosphoric acid solution, then raise the temperature to 98 °C and keep it for 2 h to obtain white slurry B; (7) After filtering, washing and drying, slurry B is used to obtain titanium-doped iron phosphate dihydrate. After calcining, the iron phosphate dihydrate is used to obtain anhydrous iron phosphate with high purity and high compaction density.
[0061] Figure 7 Scanning electron microscope image of iron phosphate dihydrate prepared for experiment 3, Figure 8 Scanning electron microscope image of iron phosphate dihydrate prepared for experiment 3, Fig. 9 This is the particle size distribution diagram of anhydrous iron phosphate prepared in Experiment 3; its characteristics are similar to those of Experiment 1 and Experiment 2. Figure 7-9 It can be seen that the primary particles of ferric phosphate dihydrate prepared in Experiment 3 aggregate into flaky agglomerates, and the flaky particles are stacked on each other to form a cluster structure; the primary particles of anhydrous ferric phosphate are melt-bonded to form a porous network structure; the particle size distribution is bimodal, with a complex of large and small particles.
[0062] Experiment 4 This experiment is similar to the steps of Experiment 1, and the reaction ratio is the same. The difference lies in the different feeding methods in the synthesis stage, that is, ferrous salt is used as the base, and phosphate salt, hydrogen peroxide, and titanium sulfate are fed in three streams at the same time. The specific steps are as follows: (1) Weigh 2.76 kg of ammonium dihydrogen phosphate, dissolve it and dilute it to 15 L to obtain a phosphate solution; weigh 6.67 kg of ferrous sulfate heptahydrate, dissolve it and dilute it to 20 L to obtain a ferrous salt solution; (2) controlling the pH of the ferrous salt solution to 2.0 by adding concentrated sulfuric acid solution; (3) While stirring continuously, add concentrated ammonia water to the above phosphate solution in small amounts and in multiple times to control the pH of the phosphate solution to 7.3, and finally add pure water to make up to 20 L; (4) Weigh 31.10 g of titanium sulfate, add 500 mL of pure water, and stir for 20 min until it is completely dissolved to obtain a titanium sulfate solution; (5) Weigh 1.77 kg of 30 wt% hydrogen peroxide for later use; (6) The ferrous salt solution was heated to 50°C, and under continuous stirring, the phosphate solution, hydrogen peroxide solution, and titanium sulfate solution were added simultaneously within 30 minutes to qualitatively detect whether all the ferrous ions were oxidized to trivalent ferrous ions; the mixture was then reacted for 30 minutes to obtain slurry A; (7) After the reaction is completed, the slurry A is preliminarily washed in a centrifuge and dried at high speed to obtain a filter cake A; (8) Add a certain amount of pure water to the filter cake A and continue stirring until the slurry is uniform. Then, add 830.12 g of 80 wt % phosphoric acid solution and heat to 98 °C for 1.5 h to obtain a white slurry B. (9) After filtering, washing and drying, slurry B is used to obtain titanium-doped iron phosphate dihydrate. After calcining, the iron phosphate dihydrate is used to obtain high-purity and high-density anhydrous iron phosphate.
[0063] The microstructures of the dihydrated iron phosphate and anhydrous iron phosphate prepared in this experiment are as follows: Fig.10 , 11 As shown, the particle size distribution of anhydrous ferric phosphate is as follows Fig.12 As shown, the primary particles of dihydrate ferric phosphate are significantly smaller than those in Experiment 1, and the primary particles are aggregated into fine fragments and rolled into loose balls, with serious rolling phenomenon; the primary particles of anhydrous ferric phosphate are melt-bonded to form a porous network structure; the particle size distribution is bimodal, but small particles are the majority.
[0064] Experiment 5 This experiment is similar to the steps of Experiment 1, with the same reaction ratio. The difference lies in the different feeding methods in the synthesis stage, that is, ferrous salt is used as the base, phosphate salt and titanium sulfate are added in two streams, and hydrogen peroxide is added later. The specific steps are as follows: (1) Weigh 2.76 kg of ammonium dihydrogen phosphate, dissolve it and dilute it to 15 L to obtain a phosphate solution; weigh 6.67 kg of ferrous sulfate heptahydrate, dissolve it and dilute it to 20 L to obtain a ferrous salt solution; (2) controlling the pH of the ferrous salt solution to 2.0 by adding concentrated sulfuric acid solution; (3) While stirring continuously, add concentrated ammonia water to the above phosphate solution in small amounts and in multiple times to control the pH of the phosphate solution to 7.3, and finally add pure water to make up to 20 L; (4) Weigh 31.10 g of titanium sulfate, add 500 mL of pure water, and stir for 20 min until it is completely dissolved to obtain a titanium sulfate solution; (5) Weigh 1.77 kg of 30 wt% hydrogen peroxide for later use; (6) The ferrous salt solution was heated to 50°C, and under continuous stirring, the phosphate solution and the titanium sulfate solution were added simultaneously within 60 minutes, and hydrogen peroxide was added within 60 minutes to qualitatively detect whether all the ferrous ions were oxidized to trivalent ferrous ions; the mixture was reacted for 30 minutes to obtain slurry A; (7) After the reaction is completed, the slurry A is preliminarily washed in a centrifuge and dried at high speed to obtain a filter cake A; (8) Add a certain amount of pure water to the filter cake A and continue stirring until the slurry is uniform. Then, add 830.12 g of 80 wt % phosphoric acid solution and heat to 98 °C for 2 h to obtain white slurry B. (9) After filtering, washing and drying, slurry B is used to obtain titanium-doped iron phosphate dihydrate. After calcining, the iron phosphate dihydrate is used to obtain high-purity and high-density anhydrous iron phosphate.
[0065] The microstructures of the dihydrated iron phosphate and anhydrous iron phosphate prepared in this experiment are as follows: Fig.13 , 14 As shown, the particle size distribution of anhydrous ferric phosphate is as follows Fig.15 As shown, the primary particles of dihydrate ferric phosphate are significantly larger than those in Experiment 1, and are convoluted into loose spherical agglomerates; the primary particles of anhydrous ferric phosphate are melt-bonded to form a porous network structure; and the particle size distribution is unimodal.
[0066] Experiment 6 The anhydrous iron phosphate precursors prepared in Experiment 1 (the present invention), Experiment 2 (the present invention), Experiment 3 (the present invention), Experiment 4, and Experiment 5 were made into lithium iron phosphate materials and button batteries, and their powder compaction density and electrochemical properties were tested. The test results are shown in Table 1.
[0067] Table 1 Performance test results of iron phosphate and lithium iron phosphate
[0068] As shown in Table 1, after the iron phosphate prepared in Experiment 1 (the present invention), Experiment 2 (the present invention), and Experiment 3 (the present invention) were made into lithium iron phosphate, the compacted density of the powders reached 2.613, 2.556, and 2.558 g / cm, respectively. 3 , and the 0.1C and 1C discharge capacities are maintained at a high level.
[0069] The lithium iron phosphate prepared by the iron phosphate in Experiment 4 can reach a powder compaction density of 2.568 g / cm 3 , but its 1C discharge capacity is only 124.51 mAh / g; the lithium iron phosphate made from iron phosphate in Experiment 5 can reach a 1C discharge capacity of 130.62 mAh / g, but its powder compaction density is only 2.466 g / cm 3 It can be seen that Experiments 4 and 5 cannot maintain the balance between the higher powder compaction density and higher discharge capacity of the lithium iron phosphate end. At present, this phenomenon is attributed to the inherent differences caused by the different feeding methods in the wet synthesis stage.
Claims
1. A low-cost preparation method for high-performance titanium-doped iron phosphate, characterized in that: The following steps are involved: S1, respectively prepare 40-85 wt% phosphoric acid solution, 10-25 wt% hydrogen peroxide solution, phosphate solution and ferrous salt solution for standby use; The concentration of phosphorus in the phosphate solution is 0.8-1.3 mol / L; The concentration of iron in the ferrous salt solution is 0.8-1.3 mol / L; S2. Add titanium sulfate directly to the ferrous salt solution, stir evenly, and control the solution pH to 2.0-3.0 to obtain an iron-titanium mixed solution; S3, directly add ammonia water to the phosphate solution, stir evenly, control the solution pH to 5.95-6.05, add hydrogen peroxide solution to obtain a phosphorus-oxygen mixed solution; S4. Under continuous stirring, the temperature of the iron-titanium mixed solution is raised to 40-60° C., and a phosphorus-oxygen mixed solution is added to gradually oxidize all ferrous ions into trivalent ferrous ions. After reacting for 30 minutes, slurry A is obtained. S5, slurry A is initially filtered and washed to obtain filter cake A; S6. Under continuous stirring, add pure water and phosphoric acid solution to the filter cake A, then raise the temperature to 80-100° C., and keep the temperature for 60-120 min after the slurry color changes to white, to obtain white slurry B; S7. After filtering, washing and drying the slurry B, titanium-doped iron phosphate dihydrate is obtained. After calcining the iron phosphate dihydrate, high-purity and high-density anhydrous iron phosphate is obtained.
2. A low-cost preparation method for high-performance titanium-doped ferric phosphate according to claim 1, characterized in that: In step S1, the phosphate solution is prepared from one or any combination of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.
3. The low-cost preparation method of a high-performance titanium-doped ferric phosphate according to claim 1, characterized in that: In step S1, the phosphate solution is prepared from phosphoric acid, and ammonia water or liquid alkali is added to adjust the pH value to 4.0-6.
0.
4. The low-cost preparation method of high-performance titanium-doped ferric phosphate according to claim 1, characterized in that: In step S1, the ferrous salt solution is prepared from one or any combination of ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder, and iron sheet.
5. The low-cost preparation method of high-performance titanium-doped ferric phosphate according to claim 1, characterized in that: In step S2, the pH value of the iron-titanium mixed solution is controlled by a sulfuric acid solution.
6. The low-cost preparation method of high-performance titanium-doped ferric phosphate according to claim 1, characterized in that: In step S3, the pH value of the phosphate solution is controlled by ammonia water; the molar ratio of the added hydrogen peroxide to the phosphorus element in the phosphate solution is 0.6:1-0.7:
1.
7. The low-cost preparation method of high-performance titanium-doped ferric phosphate according to claim 1, characterized in that: In step S4, the phosphorus-oxygen mixed solution is added within 50-60 minutes.
8. A low-cost preparation method for high-performance titanium-doped ferric phosphate according to claim 7, characterized in that: In step S4, the molar ratio of iron element to phosphorus element in the iron-titanium mixed solution and the phosphorus-oxygen mixed solution is 1:0.9-1:1.
1.
9. The low-cost preparation method of high-performance titanium-doped ferric phosphate according to claim 1, characterized in that: In step S5, the conductivity of the washing water of the slurry A after preliminary filtration and washing is ≤2000 μS / cm.
10. The low-cost preparation method of high-performance titanium-doped ferric phosphate according to claim 1, characterized in that: In step S6, the molar ratio of phosphorus in the phosphoric acid solution to iron in the slurry A solution should be controlled to n(P):n(Fe)=0.2:1-0.4:1; The heating time is 90-110 min.
Citation Information
Patent Citations
Preparation method of iron phosphate for high-purity high-pressure solid lithium iron phosphate
CN109775679A
Cited By
Process method for producing titanium-doped iron phosphate by one-step method
CN120987293A
Method for preparing titanium-doped iron phosphate
CN121990543A
A method for preparing titanium-doped iron phosphate
CN121990543B
Preparation method of blocky monocrystal iron phosphate
CN122013292A
Preparation method of titanium-doped iron phosphate capable of keeping stable iron-phosphorus ratio and product of titanium-doped iron phosphate
CN122233345A